The Dimension of Religion in Political Conflict and Violence: An Experience In Indonesia - Rasidin, Mhd.; Ramdhani, Indra; Ilahi, Restu Prana; Busni, Darti; Witro, Doli; Alghani, Raid (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article aims to discuss the religious dimension in political conflict and violence in Indonesia Indonesian society is heterogeneous, especially in religious affiliation. A series of cases of violence in Indonesia involving religion, such as the events in Pekalongan (1995), Situbondo (1996), Poso (1998), Ambon (1999), Tasikmalaya (1996), Sukabumi (2008), and also other violence in several parts of Indonesia . This incident caused various kinds of losses both in terms of community facilities and the many casualties that fell. This is based on an excessive commitment to the religious aspects of Indonesian society... The method used in this article is a qualitative research method that consists of library research. Thus, the data obtained comes from literary sources such as books, scientific articles, research reports, and so on. The data analysis technique is a qualitative data analysis technique of Miles et al. The results of the study show that the religious dimension is the main factor in the various events of political conflict and violence in Indonesia. These religious-based conflicts are used by political elites to gain political power. The various religious and political conflicts and violence is due to hyper commitment in most religious societies and the factor of religious differentiation.Â